A STUDY ON BIPOLAR AFFECTIVE DISORDER SUBJECTS UNDER REMISSION – QUALITY OF SLEEP AND QUALITY OF LIFE - S, Thirumalai; R, Ravikumar; M, Kathir; SURESH BABU P (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: People affected with bipolar disorder experience sleep disturbances which precedes an episode of depression or mania. The aim of the present study was to assess the quality of sleep and quality of life (QOL) in subjects with euthymic bipolar disorder. Methods: This was a case–control study conducted between April 2015 and September 2015. All subjects in the age of 18–60 years with bipolar affective disorder (BPAD) under remission for at least 6 months were included as cases and healthy volunteers as controls. Mini-international neuropsychiatric interview plus brief interview, Hamilton depression rating scale and young mania rating scale were used to quantify remission. Pittsburgh sleep quality index (PSQI) and Epworth sleepiness scale were used to assess quality of sleep and the WHO quality of life brief version (WHOQOL-BREF) scale was used to assess QOL. Descriptive data were given in summary statistics, Student’s t-test to compare means, one-way ANOVA to compare means with variables, Pearson’s test for correlation and Chi-square test for qualitative variables were used. p<0.05 was considered significant. Results: Fifty patients and 51 volunteers were included in the study. The mean age was 39.62±11.68 years, males and females were equal, most were married (82.17%), 34.65% had completed high school, 47.52% were unskilled workers and 73.27% were in upper lower socioeconomic status. About 95.05% did not had family history of psychiatric illness. Euthymic BPAD patients were more unmarried (p=0.033), more unemployed (p=0.0003), less full-time employees (p=0.0001), had more PSQI global score (p=0.0003) and more Epworth sleepiness scale (p=0.0004) than controls. As the duration of remission increased, sleep dysfunction improved (p=0.009). WHOQOL scores were lower in BPAD patients and overall perception of health was lower (p=0.044). BPAD patients had poor sleep hygiene and watched more television in bed, had more cigarettes and had more coffee than tea. Conclusion: Patients with BPAD even when in remission had significant sleep disturbances. Sleep hygiene factors have to be modified to improve sleep dysfunction. Psychosocial interventions are needed to achieve better QOL.